Cuba, United States and fight against drug trafficking: ups and downs of a necessary cooperation - Santiago E. Bejerano (Ибероамериканские тетради)
Given the geostrategic importance of Cuba for the entire American continent and the increasing complexity of the nature of security as such, and accordingly, of the mechanisms of ensuring it in the modern world, the problem of drug trafficking is rather high on the agenda of the U.S.-Cuban relations. The article examines the issue of combating drug trafficking in the context of bilateral relations between Cuba and the United States in order to assess the prospects for joint efforts on this track. The author presents a retrospective of mostly unilateral initiatives by U.S. presidents that did not lead to real tangible results, in particular due to the prevailing erroneous approach of militarization in the fight against drug trafficking. The new century requires new forms and a qualitatively higher level of interaction. With a noticeable warming in the dialogue with Cuba under Barack Obama the situation has changed in many respects, and quite a few initiatives of bilateral nature began to bear fruit. Nevertheless, with Donald Trump’s rise to power, there is an obvious setback in the rapprochement, in proof of which the author gives examples of specific destructive steps, although this position of the administration met if not open criticism, then proposals for alternative scenarios of the development of contacts between the states. The potential that exists in both countries for cooperation in this area can be realized provided that the interests of common security prevail over political disagreements and state channels of cooperation are strengthened, with the dynamics of this process being reflected in the situation in the region as a whole.